Comprehensive immune landscape of lung-resident memory CD8+ T cells after influenza infection and reinfection in a mouse model - Jia, Ju; Li, Hui; Huang, Zhisheng; Yu, Jiapei; Zheng, Ying; Cao, Bin (Frontiers in Microbiology, 2023)
Background: Resident phenotypic memory CD8+ T cells are crucial for immune defense against pathogens. However, little is known about the potential transitions and regulation mechanisms of their function after influenza virus infection and reinfection. In this study, we utilized integrated transcriptome data and in vivo experiments to investigate the key characteristics behind. Methods: Two single-cell RNA sequencing (scRNA-seq) datasets of lung CD8+ T cells and one RNA-seq dataset of lung tissue after infection or reinfection were included. After Seurat procedures classifying CD8+ T subsets, the scCODE algorithm was used to identify the differentially expressed genes for GSVA, GO and KEGG pathway enrichment. Monocle 3 and CellChat were used to infer pseudotime cell trajectory and cell interactions. The ssGSEA method was used to estimate the relative proportions of immune cells. And the findings were confirmed with a mouse model via flow cytometry, RT-PCR analysis. Results: Our study refined the landscape of CD8+ T cell subsets in the lung, showing that CD8+ Trm cells accumulated in the lung within 14 days after influenza infection. The classical CD8+ Trm cells co-expressed high level of CD49a and maintained even 90 days. The ratio of CD8+ Trm cells decreased one day after influenza reinfection, which may parallel with their potential transition into effector types, as observed in trajectory inference analysis. KEGG analysis suggested that PD-L1 expression and PD-1 checkpoint pathway was upregulated in CD8+ Trm cells on day 14 after infection. GO and GSVA analyses revealed PI3K-Akt-mTOR and type I interferon signaling pathway were enriched in CD8+ Tem and Trm cells after reinfection. Additionally, CCL signaling pathways were involved in cell interaction between CD8+ Trm cells and other cells, with Ccl4-Ccr5 and Ccl5-Ccr5 ligand/receptor pairs being important between CD8+ Trm and other memory subsets after infection and reinfection. Conclusions: Our data suggest that resident memory CD8+ T cells with CD49a co-expression account for a large proportion after influenza infection, and they can be rapidly reactivated against reinfection. Function differences exist in CD8+ Trm and Tem cells after influenza infection and reinfection. Ccl5-Ccr5 ligand/receptor pair is important in cell interactions between CD8+ Trm and other subsets.